2010
DOI: 10.1167/iovs.09-5109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Mutations in the Ortholog ofDrosophilaEyes Shut Gene (EYS) Causing Autosomal Recessive Retinitis Pigmentosa

Abstract: This is the first report of molecular genetic analysis of EYS in a cohort of unrelated British and Chinese patients with RP. The results further the initial hypothesis that EYS is a major causative gene for recessive RP and emphasize the role of different types of mutations in disrupting the function of EYS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 18 publications
4
52
1
Order By: Relevance
“…The IBD and celiac disease associations share the same direction of effect, but the asthma and eosinophil count SNPs have opposite directions of effect. The EYS SNP rs665873 has low frequency (HapMap CEU MAF=0.051) but is in tight LD with the common (MAF=0.43) statin-myopathy associated SNP rs3857532[36], (D’=0.91, r2=0.01, source:1000 genomes), and with six SNPs associated with retinitis pigmentosa[30] (D’=1, r2=0.001) (Supplementary Table 7). The AAU, statin-myopathy and retinitis pigmentosa SNPs all have the same direction of effect.…”
Section: Resultsmentioning
confidence: 99%
“…The IBD and celiac disease associations share the same direction of effect, but the asthma and eosinophil count SNPs have opposite directions of effect. The EYS SNP rs665873 has low frequency (HapMap CEU MAF=0.051) but is in tight LD with the common (MAF=0.43) statin-myopathy associated SNP rs3857532[36], (D’=0.91, r2=0.01, source:1000 genomes), and with six SNPs associated with retinitis pigmentosa[30] (D’=1, r2=0.001) (Supplementary Table 7). The AAU, statin-myopathy and retinitis pigmentosa SNPs all have the same direction of effect.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study on 100 Japanese arRP patients indicated very likely pathogenic mutations and possible pathogenic mutations in 18% (18/100) and 8% (8/100), respectively, of the study population; these values are higher than those previously reported. [4][5][6][7] Our previous study has shown that 16% of Japanese patients with arRP displayed either the c.4957_4958insA or the c.8868C4A mutation, which accounted for 57% (15 þ 5/35) of the mutated alleles and seem to be frequent among Japanese patients with arRP. 8 However, a detailed haplotype analysis of the EYS gene has not been performed, and therefore, currently, we cannot verify whether each mutation occurred in an ancient common ancestor.…”
Section: Discussionmentioning
confidence: 95%
“…2,3 EYS gene mutations, which include primarily truncating and some missense mutations, have been detected in arRP-affected families of different ancestral origin and are reported to account for 5-16% of arRP cases. [4][5][6][7] Recently, we screened all EYS gene exons in 100 unrelated Japanese RP patients and, found EYS gene mutations in at least 20% of the arRP patients (see the Supplementary Table in the Supplementary Material -available online). 8 In the current study, we examined the clinical features of ten unrelated Japanese patients with RP caused by the EYS gene mutation and compared the phenotype of four patients with the homozygous c.4957_4958insA (p.S1653KfsX2) mutation, which is a major causative mutation of RP in Japan, to that of the other RP patients.…”
Section: Introductionmentioning
confidence: 99%
“…The autosomal recessive retinitis pigmentosa 25 (RP25, OMIM #612424) is caused by abnormal EYS (Abd El-Aziz et al, 2008; Collin et al, 2008), a secreted extracellular matrix protein, in several populations worldwide (Abd El-Aziz et al, 2008, 2010; Audo et al, 2010; Bandah-Rozenfeld et al, 2010; Barragán et al, 2010; Chen et al, 2015; Collin et al, 2008; Di et al, 2016; Hosono et al, 2012; Littink et al, 2010b). Mutations in EYS account for 5-16% of all autosomal recessive cases in Europe (Audo et al, 2010; Barragán et al, 2010; Littink et al, 2010b) and the most prevalent form of inherited retinal dystrophy in Japan (Arai et al, 2015; Iwanami et al, 2012).…”
Section: Introductionmentioning
confidence: 99%